Evidence that semaphorin 4D is upregulated in neurons in Huntington's and Alzheimer's diseases: Effects of a SEMA4D blocking antibody on FDG‐PET in a clinical trial, and treatment rationale for its use in AD: Human/Human trials: Other. (7th December 2020) - Evans, Elizabeth E.; Fisher, Terrence L.; Leonard, John E.; Reader, Alisha M.; Mishra, Vikas; Mallow, Crystal L.; Balch, Leslie; Howell, Alan; Smith, Ernest S.; Feigin, Andrew; Siemers, Eric R.; Zauderer, Maurice
Abstract: Background: Pepinemab (VX15/2503) is a humanized IgG4 monoclonal antibody that blocks the binding of semaphorin 4D (SEMA4D) to its plexin B1 and plexin B2 receptors. SEMA4D is upregulated in neurons and oligodendrocytes in response to stress and triggers inflammatory activation of plexin B1/B2 positive astrocytes with concomitant loss of some normal astrocyte functions. Blocking antibody to SEMA4D has been shown to reduce neurodegenerative processes in preclinical models, including Huntington's disease (HD) and Alzheimer's disease (AD). SIGNAL‐HD is a double‐blind, placebo‐controlled study of pepinemab in HD. Given previous studies of fluorodeoxyglucose (FDG) positron emission tomography (PET) loss in HD and the mechanism of action of pepinemab, FDG‐PET imaging was included in the SIGNAL‐HD study. Method: Transgenic mouse models for HD (Q175) and AD (CVN) as well as human pathological tissue was used for immunohistochemistry. The SIGNAL‐HD study includes participants with late prodromal and early manifest HD. Results from 36 subjects in Cohort A informed group size and treatment duration in Cohort B. A subset of participants in Cohort A underwent PET scanning using FDG at baseline, at the end of the 6‐month placebo‐controlled period and at 12 months at the end of the open‐label treatment period. Result: SEMA4D was upregulated and astrocyte activation was present for HD and AD based on samples from transgenic models and staged patient autopsy samples. SIGNAL‐HD Cohort A (n=36) has been completed and Cohort B (n=265) is fully enrolled. For participants in Cohort A undergoing FDG‐PET imaging (n=19), those in the pepinemab group showed increases in FDG uptake compared to baseline (median 8.6%, range: 0.5‐20.4%) while participants taking placebo showed the expected decrease after 6 months. Nominal statistical significance (p<0.05) pepinemab compared to placebo was achieved for 11/14 frontal and parietal brain regions. Conclusion: Transgenic mouse models and human neuropathological analyses are consistent with an upregulation of SEMA4D in HD and AD. The increase in FDG‐PET signal in SIGNAL‐HD Cohort A suggests central target engagement and improvement in brain metabolic activity. SIGNAL‐AD, a randomized, placebo‐controlled, phase 1b/2 study of pepinemab in early AD, will also incorporate FDG‐PET and is planned to begin mid‐2020.